A Structuralist Model of the Small Open Economy in the Short, Medium and Long Run - Hoon, Hian Teck (Institutional Knowledge at Singapore Management University, 2005)
In open-economy macroeconomics there is a monetary model in the Keynesian tradition that is deemed serviceable for analyzing the short run and there is a nonmonetary neoclassical theory thought capable of handling the long run. But do the Keynesian and neoclassical models meet the challenges thrown out by the main events of the past few decades¡ªthe '80s shock to Europe taking the form of an external jump in real interest rates; the sort of shock experienced in the U.S. and parts of northern Europe in the second half of the '90s: the emerging prospect of new industries in the future creating increased needs for capital; and what may have been a major shock of the '60s: the large Kennedy tax cut, mostly the reduction in income taxes, enacted in the U.S. in 1964? We suggest that the effects of these shocks on the open economy are not well portrayed by either the standard Keynesian model or by standard neoclassical theory. We then provide a careful development of a nonmonetary model of the equilibrium path of the real exchange rate, and natural output, employment and interest based on trading frictions in the goods market, and compare its implications not only over the medium run but for the short run and the long run as well.